THE QUR'ANIC THERAPEUTIC SPIRITUAL COMMUNICATION ON THE PATIENT'S SPIRITUAL PROBLEMS IN NURSING CARE - Zaenal Arifin, Mohamad; Suliyono, Suliyono; Ghofur, Abdul; Askan, Fatimah (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2022)
This paper discusses the Qur'anic therapeutic, spiritual communication, which is used as an approach to dealing with spiritual problems experienced by patients. In suffering from illness, patients, in addition to needing medical treatment, also need help, guidance, and spiritual services to overcome the psychological shock they experience and support their illness's healing process. This research is library research using a descriptive-analytical approach. Research data is sourced from literature books, journals, books of interpretation, and others that correlate with the discussion. The results of this study indicate that the therapeutic Qur'anic spiritual communication becomes a model for healing the patient's spiritual problems. Delivery of messages containing Qur'anic spirituality by nurses to patients who are strengthened by the ability to express words that are clear, evocative, polite, gentle, helpful, and pleasant, as well as profound experiences of spiritual healing will be a healing power for patients' spiritual problems. Moreover, the spiritual maturity of nurses is no less critical, which is reflected when providing services to patients in the form of showing care, compassion, listening, sincerity, being friendly, smiling, and being patient with the patient's condition. Likewise, do not be arrogant, arrogant, rude, find fault, or indulge in patient disgrace and the like.